Origins, Assumptions and Reception of the German Schwerter Konsent: The Role of Religious Education Teachers in Discussing Controversial Issues - Herbst, Jan-Hendrik (Paedagogia Christiana, 2025)
This article presents the genesis, basic assumptions and reception of the socalled Schwerter Konsent, which formulates didactic foundations for the discussion of controversial issues in religious education in Germany. Although its content is rooted in the German-speaking debate, it has also been adopted in other countries, such as Spain. The Schwerter Konsent defines the guiding principles of Christian religious education in public schools, which is oriented towards controversy, maturity and critical faculties, and counteracts the indoctrination of pupils.